Sustainability Index of Benoa Bay Beach Reclamation Against National Resistance - Munawar Ali (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
This study aims to analyze systematically and thoroughly about how the impact of coastal reclamation on National Resilience. The activity starts from a thorough understanding of the system that occurs in the reclamation and variable processes that affect national security. The research method used analysis Multi-Dimensional Scaling Method. The Benoa Bay reclamation activity plan, multi-dimensional analysis is not or less sustainable, with an index of 42.93 %. The most sensitive attribute influences the dimensions of the environment, is the attribute of potential sedimentation is the most sensitive attribute with a value of 0.13. The most sensitive attribute affecting the economic dimension is an increase in regional revenue. In the sensitivity test of the socio-cultural dimension, the most sensitive and influential attribute obtained is the perception of the community shop. The most sensitive attribute influencing the legal dimension is the formal rules, there must be formal rules, indeed administratively the formal rules are legal products that are approved by the institutions governed by the law, but usually what is forgotten is the process of realizing formal rules.